1972
DOI: 10.1121/1.1913238
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Speech: Some Acoustical Correlates

Abstract: This paper describes some further attempts to identify and measure those parameters in the speech signal that reflect the emotional state of a speaker. High-quality recordings were obtained of professional "method" actors reading the dialogue of a short scenario specifically written to contain various emotional situations. Excerpted portions of the recordings were subjected to both quantitative and qualitative analyses. A comparison was also made of recordings from a real-life situation, in which the emotions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
339
1
27

Year Published

1981
1981
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 635 publications
(381 citation statements)
references
References 2 publications
14
339
1
27
Order By: Relevance
“…174-177) and Alpert et al (1989). Classic work on the acoustics of emotion was done by Williams and Stevens (1972). Spoerri (1966) cites with approval an observation by C. Cherry that even when not demonstrably aprosodic, patients with schizophrenia often sound like a person talking on the telephone (in a day when telephones were less familiar and had poorer sound quality than today): the intonation and loudness are more constant, as if the hearer's response were not available for the speaker to adjust to it.…”
Section: Prosody (Timing and Intonation)mentioning
confidence: 99%
“…174-177) and Alpert et al (1989). Classic work on the acoustics of emotion was done by Williams and Stevens (1972). Spoerri (1966) cites with approval an observation by C. Cherry that even when not demonstrably aprosodic, patients with schizophrenia often sound like a person talking on the telephone (in a day when telephones were less familiar and had poorer sound quality than today): the intonation and loudness are more constant, as if the hearer's response were not available for the speaker to adjust to it.…”
Section: Prosody (Timing and Intonation)mentioning
confidence: 99%
“…Listeners were able to select the appropriate utterance at (only slightly) better than chance accuracy in both normal and whispered speech. Williams and Stevens (1972) concluded that the pitch contour is the best indicator ofthe emotional content ofan utterance. In their review ofthe literature, Murray and Arnott (1993) noted that the most commonly referenced vocal parameters are pitch (i.e., both the average value and range of the fundamental frequency), duration, intensity, and the undefined term voice quality.…”
mentioning
confidence: 99%
“…In the literature, pitch is indicated as being one of the most relevant paralinguistic features for the detection of emotion, followed by energy, duration and speaking rate (see Bosch ten, 2003). In general, speech shows an increased pitch variability or range and an increased intensity of effort when people are in a heightened aroused emotional state (Williams and Stevens, 1972;Scherer, 1982;Rothganger et al, 1998;Mowrer et al, 1987). In a paper by Nwe et al (2003), an overview of paralinguistic characteristics of more specific emotions is given.…”
Section: Introductionmentioning
confidence: 99%